The Effects of Fintech Companies on the Performance of Banks in Indonesia - Al Hafidtz, Naufal Yosda; Satria, Dias (Contemporary Studies in Economic, Finance and Banking, 2025)
In the development of information and communication technology in the financial sector, FinTech brings innovation in financial services based on digital technology. This study aims to analyze the impact of FinTech companies, bank-specific variables and macroeconomics on bank performance in Indonesia. This study covers banks listed on LQ45 during the period 2019 to 2023 using dynamic and static panel regression model using the Generalized Method of Moments (GMM) method. The results show that Fintech has a positive effect on ROA, ROE and NPL as bank indicators. INF has a positive effect on bank performance, while GDP has a negative effect on bank performance. CTI, DG, IIS and FC have a positive effect on bank performance. However, SIZE, CAP and LLP have a negative effect on bank performance. The results of this study can provide further insight into the relationship between FinTech and bank performance, as well as a consideration for the cooperation or adoption of FinTech in banking.